Criterios para desarrollo de fortalezas tecnológicas en la UNMSM. Avances para un modelo de investigación emprendedor en ingeniería de procesos - Cachay Boza, Orestes (2016)
The study overall objective is the design of competitive advantage of Science and Technology Park plan, leaded by the Faculty of Industrial Engineering of San Marcos Major National University, considering sources of creating competitiveness to leverage the potential of research and development in UNMSM for innovation deployment in contact with the business community. For that Science and Technology Park or PCT makes a valuable contribution to knowledge and research , it has to support strategies and policies of creativity and innovation in technology products, technology incubator and new products, advanced clearinghouse oriented to development opportunities, raising the criteria for the business venture and entrepreneurship. The project PCT must generate expectations and interest in the academic and entrepreneurial environment for effective implementation, the project must have local and decentralized geographic scope, seeking greater influence space. Its implementation shall mean a valuable line of action of UNMSM in its outreach to the community and its contribution to national development, which would keep his position as main research and academic center of the country.